2022
DOI: 10.1007/s11071-022-07737-4
|View full text |Cite
|
Sign up to set email alerts
|

Cross-scale energy transfer of chaotic oscillator chain in stiffness-dominated range

Abstract: The investigations on the dynamics of hierarchical oscillator chains provide basic theories for the elds of acoustic metamaterial and passive guidance of energy ow. In the present study, the characteristics of stiffness-dominated energy transfer of a reduced cross-scale oscillator chain that generates chaotic vibrations are studied. The semi-analytical solutions are obtained by the complexi cation-averaging method and the least-square method for thoroughly searching the branches of responses. Then the energy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Systems having multiple NESs attached are even capable of exhibiting chaotic dynamics. In recent works of Chen et al [7,8], a chain of NESs were attached to a primary linear oscillator and the system was subjected to the harmonic forcing of the linear oscillator. They showed that for sufficiently high excitation amplitude the response of the system can be chaotic for specific frequency bands that depend on the excitation amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…Systems having multiple NESs attached are even capable of exhibiting chaotic dynamics. In recent works of Chen et al [7,8], a chain of NESs were attached to a primary linear oscillator and the system was subjected to the harmonic forcing of the linear oscillator. They showed that for sufficiently high excitation amplitude the response of the system can be chaotic for specific frequency bands that depend on the excitation amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…Systems having multiple NES' attached are even capable of exhibiting chaotic dynamics. In a recent work of Chen et al [7,8] a chain of NES' were attached to a primary linear oscillator and the system was subjected to the harmonic forcing of the linear oscillator. They showed that for sufficiently high excitation amplitude the response of the system can be chaotic for specific frequency bands that depend on the excitation amplitude.…”
Section: Introductionmentioning
confidence: 99%